A feasibility study on Smart Trash a chain of commercial solid waste sorting, material recovery, and transport facilities in Metro Manila - Gonzales, Edello; Moral, Ernie II
For the past three decades, economic growth in the Philippines has been fueled by rapid industrialization and urbanization. As urban areas have grown, it has brought about significant negative impacts on the environment, particularly the state of solid waste generation. Owing to its size and importance in the national economy, Metro Manila has the most pressing solid waste crisis with a massive 6,700 tons of solid waste generated everyday. Just about 720 tons, or 11 percent of these are being re-used (i.e., recycled or composted), with the remaining balance being deposited, dumped or burned just about everywhere. According to ADB (2003) study, in 30 years, the waste produced by Metro Manila will be enormous (70 million MT) that it could fill 175 times the size of the largest shopping mall in the country. Community-based and private sector initiatives are on the rise on all areas. While these initiatives have succeeded in raising awareness, and assist communities in assuming responsibility for solid waste management, their efforts remain futile as compared to the massive solid waste that has to be managed. Improvement in recycling, collection and disposal will become more critical as garbage production continues to increase with population growth and economic development. Therefore, this study was pursued to provide an analysis on the feasibility. The commercial Waste Sorting, Materials Recovery and Transport Services or Smart Trash highlights the contribution or involvement of the private sector in community-based SWM, specifically in the waste recovery effort (recycling) and waste transport. The company will be composed of several facilities located strategically per community along with its waste transport service offered to the local government. The bulk of its income will come from the fees collected from the government, and the amount of recyclables materials and biodegradable waste that it will sell to the CNG-Producing companies. The evaluation of the Company Marketing Feasibility proved the following points with regard to the market viability; 1) the market demand for the output from materials Recovery in sufficient to absorb all the output of the company; 2) the supply of waste materials from the city of Marikina for the period of 5 years follows an increasing pattern; 3) the demand for transport service in the city is existing with the demand gap in 2009 reaching almost 10% of the total capacity of Marikina City to collect (706m3); 4) the demand for biodegradable supply is sufficient to justify the transport of that particular waste to its destination with the demand reaching 753,878,521m3; and 5) there is a marketing strategy that can promote the objective and operational functions of the company through direct selling and other promotional strategies. In the Technical Feasibility Study, it was revealed that the company has the processes and technologies needed in the implementation of Smart Trash Waste Material Recovery, Recycling, and Transport Services. As for the location of the facilities, the company decided that the following sites be chosen - Sorting facility 1 (Zone I) along Gil Fernando (formerly A Tuazon), Brgy. Sta Elena; Sorting facility 2 (Zone II) along C.M. Recto St., Brgy. Nangka; and, Sorting facility 3 (Zone III) will be constructed within Brgy. Marikina Heights. As for the Central facility, it will be situated along Doña Petra, Brgy. Concepcion I. A total of 128 personnel is also needed for the company's manpower complement. The company has also satisfied the Financial and Social profitability Studies, with its 2.5 return on equity over five years, three years payback period, net present value (NPV) of PhP 32,794,067.41 and an internal rate of return (IIRR) of 42.06% for the financial, and several quantifiable benefits like stimulation of local and foreign industries, the generation of tax funds, and the creation of employment for the Social Profitability. With these individual conclusions from the different studies conducted, it can be shown that the company is a feasible venture idea.